2021
DOI: 10.1186/s11671-021-03495-1
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic, Bactericidal and Molecular Docking Analysis of Annealed Tin Oxide Nanostructures

Abstract: Nanosized tin oxide was fabricated with a simple and cost-effective precipitation technique and was analyzed by performing x-ray powder diffraction (XRD), Fourier-transform infrared (FT-IR) spectroscopy, high-resolution transmission electron (HR-TEM) microscopy, energy-dispersive x-ray (EDX) and UV–Vis spectroscopy. The XRD results revealed that tin oxide particles possessed typical orthorhombic structure and exhibited improved crystallinity with annealing. Calcination at 250 °C produced predominantly orthorho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…The extrapolation of (α h ν) 2 versus hν to zero gives the band gap energy of 3.5 eV. This value lies within the range of 3.1-3.9 eV, as mentioned in the literatures, and is comparable to the band gap energy of SnO 2 NPs synthesized using the hydrothermal method [17,40,41]. The photoluminescence (PL) spectrum was recorded with varying excitation wavelengths (l = 360~380 nm), and the spectrum of SnO 2 NPs showed an excitation wavelength of 396 and 550 nm, of which the peak at 550 nm is attributed to 6A1→4T1(4G) ligand field transition of Sn 4+ .…”
Section: Optical Properties Of Sno 2 Npssupporting
confidence: 82%
See 2 more Smart Citations
“…The extrapolation of (α h ν) 2 versus hν to zero gives the band gap energy of 3.5 eV. This value lies within the range of 3.1-3.9 eV, as mentioned in the literatures, and is comparable to the band gap energy of SnO 2 NPs synthesized using the hydrothermal method [17,40,41]. The photoluminescence (PL) spectrum was recorded with varying excitation wavelengths (l = 360~380 nm), and the spectrum of SnO 2 NPs showed an excitation wavelength of 396 and 550 nm, of which the peak at 550 nm is attributed to 6A1→4T1(4G) ligand field transition of Sn 4+ .…”
Section: Optical Properties Of Sno 2 Npssupporting
confidence: 82%
“…Among many photoactive metal oxide nanoparticles, SnO 2 nanoparticles (SnO 2 NPs) have been widely studied for such purposes, and have exhibited highly photocatalytic activity with a band gap energy of about 3.2-3.6 eV. SnO 2 also offers and gives higher electron mobility (100-200 cm 2 V −1 s −1 ) compared to other semiconductors such as TiO 2 , leading to faster photo generated electron transport during the photocatalysis mechanism [17]. From several studies on the use of plant extracts in the SnO 2 NP synthesis, it can be concluded that different plant species gave the specific character and morphology of the nanoparticles, and influence the physicochemical character and activity [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 The selected enzyme structures were prepared for docking predictions using the method reported in our previous studies. 30,31 Docking predictions were performed using ICM Molsoft software, 32 where basic steps involved the removal of the native ligand and water of crystallization followed by the addition of polar H atoms and energy minimization. The active pocket was defined within 10 Å of the co-crystalized ligand to specify the docking position of nanocomposites in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Crystal structure of enzymes were retrieved from protein data bank with accession code 2ANQ (Resolution: 2.13 Å) [27] for DHFR E.coli , 5U0W (Resolution: 1.97 Å) for DHPS E.coli [28], and 4FGG (Resolution: 2.30 Å) for DHFR S. aureus [29]. The selected enzyme structures were prepared for docking predictions using method reported in our previous studies [30,31].…”
Section: Molecular Docking Studiesmentioning
confidence: 99%